2019
DOI: 10.5944/openpraxis.11.4.1010
|View full text |Cite
|
Sign up to set email alerts
|

Are MOOCs Open Educational Resources? A literature review on history, definitions and typologies of OER and MOOCs

Abstract: Open Education gained more visibility as a result of the emergence of Open Educational Resources (OER) and Massive Open Online Courses (MOOCs). This article discusses whether MOOCs should be considered as OER. Open Education and OER can be treated as two strands with different historical roots even though, in theory, OER are an aspect of Open Education. Different OER definitions and typologies are analyzed in relation to their dimensions and categorizations. Furthermore, the four conditions and two original ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 27 publications
0
38
0
8
Order By: Relevance
“…On 2002, UNESCO coined the term open educational resource (Cronin, 2017;Geser, 2007;Stracke, Downes, Conole, Burgos & Nascimbeni, 2019), defining it as 'the open provision of educational resources, enabled by the technologies of the information and communication, for consultation, use and adaptation of a community of users for non-commercial purposes' (UNESCO, 2002). Since then, the concept has been gaining strength in higher education institutions and international organisations such as UNESCO and OECD, due to the fact that the costs of tuition fees and textbooks have increased year after year, limiting access to information for most students in higher-level institutions.…”
Section: Open Educational Resourcesmentioning
confidence: 99%
“…On 2002, UNESCO coined the term open educational resource (Cronin, 2017;Geser, 2007;Stracke, Downes, Conole, Burgos & Nascimbeni, 2019), defining it as 'the open provision of educational resources, enabled by the technologies of the information and communication, for consultation, use and adaptation of a community of users for non-commercial purposes' (UNESCO, 2002). Since then, the concept has been gaining strength in higher education institutions and international organisations such as UNESCO and OECD, due to the fact that the costs of tuition fees and textbooks have increased year after year, limiting access to information for most students in higher-level institutions.…”
Section: Open Educational Resourcesmentioning
confidence: 99%
“…To date, the number of MOOCs, learners, and providers is still increasing continually: Despite blame as a buzzword and hype already in the year 2012, the number of offered MOOCs as well as of learners is growing today, with the main focus and popularity on educational research [7,8]. Due to its unbroken growth, this special type of OER has prompted a lot of research [9][10][11]. MOOCs prompted many authors to investigate the potential of such a so-called "disruptive innovation" [12][13][14][15], even though this innovation is not disruptive, but an adaptation of old and well-established pedagogical approaches in online learning [16].…”
Section: Introductionmentioning
confidence: 99%
“…Within that distinction, cMOOCs are mainly designed to support processes of aggregation, relationships, creation, and the sharing of knowledge, which is also known and promoted as a collaborative or connectivist approach [18] (for a critical debate on connectivism, see [19,20]). In contrast, xMOOCs are more institutionalised and rigorously structured, focused on cultural reproduction through videos and quizzes, known as a behaviourist approach [10]. However, research in the last few years has shown that such a separation and distinction cannot be made, due to the increasing overlap and mix of these two extremes [11,20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our motivation lies on the original 'Open' nature of MOOCs. The term 'Open' has been a controversial one and there have been multiple views [14]; in this work, we understand Open as no fees or requirements to sign up to a course. Based on this premise, it makes total sense that their materials would follow traditional Open Educational Resource (OER) ideas, and should be completely available to be reused by other educators and learners.…”
Section: Introductionmentioning
confidence: 99%